НЕКОТОРЫЕ АСПЕКТЫ МАЛОГО БИЗНЕСА И ЧАСТНОГО ПРЕДПРИНИМАТЕЛЬСТВА В УЗБЕКИСТАНЕ (International Journal of Innovative Technologies in Economy, 2019)
The article discusses issues of support of small business and entrepreneurship in Uzbekistan as well as service industries and their improvement. It traces the achievements and problems, and their solutions.